Decoding the enigmatic role of T-cadherin in tumor angiogenesis - Wen, Yiyang; Ma, Li; Liu, Yuanyuan; Xiong, Huabao; Shi, Dongmei (Frontiers in Immunology, 2025)
The cadherin family, which includes T-cadherin, plays a significant role in angiogenesis, a critical process involved in tumor growth, metastasis, and recurrence. T-cadherin is extensively expressed in both normal and tumor vascular tissues and has been shown to facilitate the proliferation and migration of vascular cells in some studies. However, T-cadherin also exerts inhibitory effects on angiogenesis in various tumor tissues. The functional role of T-cadherin may vary depending on the tumor type and the interaction between tumor cells and vascular cells, suggesting that it acts as a modulator rather than a primary driver of angiogenesis. Additionally, T-cadherin exhibits distinct characteristics depending on the tumor microenvironment. This review provides an overview of recent research on the role of T-cadherin in tumor angiogenesis and discusses its potential as a diagnostic or therapeutic marker in the field of tumor biology.